Relationship between pulsed wave Doppler ultrasonographic features of milk veins and CMT scores in Simmental cows - Risvanli, Ali; Dogan, Halef; Saat, Nevzat; Seker, Ibrahim (Ankara Univ Press, 2018)
This study aimed to determine the distribution of pulsed wave Doppler ultrasonographic features of milk veins in lactating cows corresponding to udder health and the results of California Mastitis Test (CMT). Clinically healthy Simmental cows aged 3-5 years within the first 12 weeks of postpartum period were used for the study. End Diastolic Velocities (EDV), Systolic Peak Velocity (SPV), and Time-Averaged Maximum Velocity (TAMV) were the measured Doppler features of the milk veins. Numerical scales for Pulsatile Index (PI) and Resistant Index (RI) were devised in accordance with blood flow parameters. The animals were allocated to two groups according to CMT results as CMT positive (n=21) and CMT negative (n=5). No differences were found between the group regarding to PI, RI, EDV, or SPV (p>0.05). However, TAMV was found to be lower in CMT-positive animals (7.52 +/- 0.85 cm/sec) compared to CMT-negative (13.90 +/- 3.56 cm/sec) animals (p=0.021).
Simental ırkı ineklerde süt veninin pulsed wave Doppler ultrasonografik özellikleri ile CMT skorunun ilişkisi
Keywords: Cow; milk vein; pulsed wave Doppler ultrasonography; udder